Economic analysis of the costs associated with Hidradenitis suppurativa at a German University Hospital - Frings, Verena Gerlinde; Schöffski, Oliver; Goebeler, Matthias; Presser, Dagmar (PLoS ONE, 2021)
Background and objectives Hidradenitis suppurativa (HS) significantly affects the patient`s quality of life and leads to multiple medical consultations. Aim of this study was to assess the utilization of medical care of HS patients. Patients and methods All patients presenting in 2017 for an outpatient, day patient and / or inpatient treatment with leading claim type HS at the Department of Dermatology, University Hospital Wurzburg, were included. Primary outcome was the economic burden of HS patients, measured by resource utilization in euro. Results The largest share of the direct medical costs for HS were the inpatient costs with a leading surgical diagnosis-related group (DRG). Antiseptics were the predominant topical prescription. While doxycycline was the most frequently prescribed systemic therapy, adalimumab was the main cost driver. The difference between in-patient (euro 110.25) and outpatient (euro 26.34) direct non-medical costs was statistically significant (p < 0.001). With regards to indirect medical costs, a statistically significantly higher loss of gross value added (inpatient mean euro 1,827.00; outpatient mean euro 203.00) and loss of production (inpatient mean euro 1,026.00; outpatient mean euro 228.00) could be noted (p < 0.001), respectively. Conclusions The present study on disease-specific costs of HS confirms that the hospital care of patients with this disease is cost-intensive. However, the primary goal of physicians is not and should not be to save costs regarding their patients`treatment, but rather the premise to utilize the existing resources as efficient as possible. Reducing the use of costly therapeutics and inpatient stays therefore requires more effective therapy options with an improved cost-benefit profile.
CRIS-Team WoS Importer:2021-08-27